Increasing the optical response of TiO2 and extending it into the visible region through surface activation with highly stable Cu5 clusters - de Lara Castells, María Pilar (2019)
The decoration of semiconductors with subnanometer-sized clusters of metal atoms can have a strong impact on the optical properties of the support. The changes induced differ greatly from effects known for their well-studied, metallic counterparts in the nanometer range. In this work, we study the deposition of Cu5 clusters on a TiO2 surface and investigate their influence on the photon-absorption properties of TiO2 nanoparticles via the computational modeling of a decorated rutile TiO2 (110) surface. Our findings are further supported by selected experiments using diffuse reflectance and X-ray absorption spectroscopy. The Cu5 cluster donates an electron to TiO2, leading to the formation of a small polaron Ti3+ 3d1 state and depopulation of Cu(3d) orbitals, successfully explaining the absorption spectroscopy measurements at the K-edge of copper. A monolayer of highly stable and well fixated Cu5 clusters is formed, which not only enhances the overall absorption, but also extends the absorption profile into the visible region of the solar spectrum via direct photo-induced electron transfer and formation of a charge-separated state.